O amor como resistência à servidão em Benedictus de Spinoza - Lima, Erika Belém (2019)
In this work, we will analyze Spinoza's ideas about the passions that lead man to servitude and fundamentally put in relief the means of resistance to this external control, so that he can be truly free. Spinoza demonstrates throughout the Ethics that it is possible to break with the passivity that conditions human beings submitting them to the terrible threat of contingent exteriority. Benedictus Spinoza's anthropology is far from possessing any kind of spiritualistic bias, since it rejects any form of mysticism, nor is it intellectualist, since knowledge alone is unable to free ourselves from bondage. It is not dualistic because it does not presents man as a composition of body and mind, sustaining a radical monism. Nor is it entirely rational because it takes desire as the essence of human beings. We can say that Spinoza's philosophy contradicts many concepts present in Western tradition. When investigating the main ideas of this Dutch thinker we are obliged to get rid of several epistemological and ontological conceptions that guided modernity. We understand that in his philosophical system, joy - although being a passion - is an affection capable of raising potency and of overcoming sad passions. In this research we argue that love, because it represents joy, is capable of guiding man in this transition and especially that it is the greatest form of resistance to servitude. To resist is to add positive forces, to resist is to fight for the emancipation of the mind from the imaginative state in which it is trapped; to resist is being able to fight, searching our own nature and gradually passing from passions to action, attaining true freedom. In Spinoza's system love represents the way of accessing freedom. It is a liberating process that leads man to happiness and can only be experienced when we achieve to know God / Nature, our affections and oneself.